Clinical patterns and outcomes of retinoblastoma in a tertiary care centre of a developing country - Moin, Muhammad; Malik, Tayyaba Gul; Siddiq, Lubna (Journal of the Pakistan Medical Association, 2023)
A retrospective study was conducted for which records of patients with Retinoblastoma (RB), treated at Lahore General Hospital between 2017 and 2021, were retrieved on February 1, 2022. Staging of RB, neuroimaging, RetCam images, and treatment were analysed. The study included 47 patients (22 females and 25 males). Mean age of presentation was 26.5 ±15 months. Records of 84 eyes (37 bilateral and 10 unilateral) were examined. Family history was positive in only (n=3) 6.3% cases. Mean follow-up was 22.94+14.4 months. Leucocoria was the commonest presentation, seen in 72 (85.7%) eyes, proptosis in 8 (9.5%), huge fungating mass in 2 (2.4%), while tumour was diagnosed because of screening in 2 (2.4%) patients. Post-treatment complications included cataract in two patients, Ischaemic chorioretinal toxicity, transient macular oedema, orbital oedema and transient intra cranial oedema in one patient each. Two patients had metastasis and underwent systemic chemotherapy. —Continue